The Proposed Warehouse Improvement Using Lean Approach to Eliminate Waste at the Main Warehouse of PT. XYZ - Danaswara Amara Dhika; Amal Witonohadi; Annisa Dewi Akbari (OPSI, 2023)
One of the grocery companies in Indonesia provides a multi-channel e-groceries digital platform for online daily shopping activities. One of the important elements that support the operational activities of an e-commerce service industry is the warehouse, which serves as a storage place for goods sold and plays a role in maintaining the quality of products before being sent to consumers. Based on observations and interviews directly with employees at the Main Warehouse, one of the causes of waste in its operational activities is the lack of optimal warehousing activities. This research aims to find out and identify waste in the Main Warehouse’s warehousing activities so that the waste that occurs can be investigated, the implementation of the Lean Warehouse approach is needed in its warehousing activities. The research began with Current State VSM with a PCE value of 47.94%, followed by Process Activity Mapping (PAM) and TIM U WOOD Assessment Questionnaire. The results of this study were obtained based on predictions after the proposed improvements were implemented, there was a reduction in processing time and the amount of waste that occurred in several operational activities at the Main Warehouse. The PCE value increased as 5.22% to 53.16% in the Future State VSM.